Evaluation of Postinfection Hearing with Audiological Tests in Patients with COVID-19: A Case–Control Study - Koparal, Mehtap; Yılmazer, Cuneyt (Journal of the American Academy of Audiology, 2021)
Background Some viral infections can cause congenital or acquired unilateral or bilateral hearing loss. It is predicted that the coronavirus disease 2019 (COVID-19) virus, which can affect many systems in the body, may also have a negative effect on hearing.Purpose This study evaluated the effects of COVID-19 infection on pure-tone average.Research Design A case–control study.Materials and Methods A total of 104 volunteers (48 control, 56 experimental group) who applied to the ENT clinic of Adıyaman University Training and Research Hospital were included in this study. After the detailed clinical examination and medical history, 13 volunteers of the experimental group and 5 volunteers from the control group were excluded from the study. In this way, each group consisted of 43 volunteers. While the experimental group consisted of patients who did not have any hearing problems before but had COVID-19. The control group consisted of healthy volunteers who did not have any hearing problems and were not infected with COVİD-19. Audiological test was applied to all volunteers to determine their pure-tone average. On the data obtained, it was analyzed whether COVID-19 affects the pure-tone average and how it changes according to variables such as age and gender.Results The evaluation of the 43 (50.0%) COVID-19-positive patients and 43 (50.0%) healthy controls showed no significant differences (p > 0.05) at 250 and 500 Hz, whereas at 4000, 6000, and 8000 Hz, the two groups differed significantly. In addition, significant differences were found in the left and right ears at 1000 and 2000 Hz (p < 0.05). The differences between the two groups in the pure-tone average of the left and right ear were statistically significant (p < 0.05). However, there were no significant sex-based differences in the pure-tone average between males and females (p > 0.05)Conclusion The pure-tone average of COVID-19 positive patients was significantly worse than those of the healthy control group. Thus, COVID-19 should also be considered in patients presenting with unexplained hearing loss. Further studies should investigate the effects of COVID-19 on hearing and the underlying pathophysiology.
Keywords: COVID-19; hearing loss; cochlea function; audiometry